Do Stronger Intellectual Property Rights Increase International Technology Transfer? Empirical Evidence from U. S. Firm-Level Panel Data - Branstetter, Lee G.; Fisman, Raymond; Foley, C. Fritz (Quarterly Journal of Economics, 2006)
One of the alleged benefits of the recent global movement to strengthen intellectual property rights (IPRs) is that such reforms accelerate transfers of technology between countries. The paper examines how technology transfer among U.S. multinational firms changes in response to a series of IPR reforms undertaken by 12 countries over the 1982-99 period. The analysis of detailed firm-level data reveal that royalty payments for intangibles transferred to affiliates increase at the time of reforms, as do affiliate research and development (R&D) expenditures and total levels of foreign patent applications. Increases in royalty payments and R&D expenditures are more than 20 percent larger among affiliates of parent companies that use U.S. patents more extensively prior to reform and therefore are expected to value IPR reform most.